Water Quality Assessment along With Pollution Sources of the Halda River (Journal of the Asiatic Society of Bangladesh, Science, 2017)
In the present study water quality assessment and land based sources of pollutants discharged into the Halda River through four major canals were investigated. The ranges of pH, DO, BOD, NO3-N, PO4-P, chloride and total alkalinity of the collected samples varied from 7.1-8.8, 3.35-4.70 mg/L, 0.055-5.0 mg/L, 0.12-3.1 mg/L, 0.06-0.16 mg/L, 8.4-69.30 mg/L and 73-220 mg/L, respectively. pH, DO, BOD showed significant changes at Mondakini Canal and Chengkhali Canal for monsoon, post-monsoon and winter (p